Tales of the Body: An Ethnographic Study of Illness Narratives among Patients with Diabetes in Eswatini - Maleka, Skhanyiso Lesedi (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.